Media dealing with the infodemic in the context of the Corona pandemic - Yahia BENLARBI (Social Sciences Journal, 2021)
This research paper sought to study the dynamic nature of fake news and how journalists in Algeria deal with the health epidemic and the infodemic in the context of the emerging coronavirus, using the descriptive approach and the interview tool with an intentional sample of journalists.         The results showed the that disinformation, misinformation, and fake news is an infodemic at the time of the emerging Corona virus, while the opinions of journalists differed among professional advocates The Algerian media in addressing the infodemic and criticizing its role in the production and dissemination of the phenomenon, in the absence of specialized scientific journalism and the need to develop journalists' skills in verifying and examining the authenticity of digital content.